Role of Anthracycline in the Therapy of Breast - Prayogo, Nugroho (Indonesian Journal of Cancer, 2008)
Role of Anthracycline in the Therapy of BreastÂ full text: http://www.scribd.com/doc/45153335/Role-of-Anthracycline-in-the-Therapy-of-Breast